Hybrid fiber reinforced concrete-filled square stub columns under axial compression. (1st November 2019) - Guler, Soner; Yavuz, Demet; Aydın, Muhammet
Highlights: Concrete filling significantly improves the axial load, ductility and toughness capacities of hollow CFAT, CFCST, and CFSST columns. The effects of steel and synthetic fibers on axial load and pre-peak toughness capacities of CFAT, CFCST, and CFSST columns are highly limited. The effects of steel and synthetic fibers on ductility and post-peak toughness capacities of CFCST and CFSST columns are significant. The use of steel and synthetic fibers is much more effective to improve the post-peak behavior of the CFCST and CFSST columns than the CFAT columns. Abstract: The main aim of this study is to compare the axial load, ductility, and toughness capacities of square concrete-filled carbon steel (CFCST), stainless steel (CFSST) and aluminum tube (CFAT) columns filled with plain concrete, single (steel) and hybrid (steel + synthetic) fiber-reinforced concrete under axial compression. To this end, the enhancement in axial load, ductility and toughness capacities of steel and hybrid fiber-reinforced CFCST, CFSST, and CFAT columns were obtained with regard to fiber volume ratio (0.5 and 1.5%), compressive strength of concrete (30 and 70 MPa) and the steel tube thickness (2, 3 and 4 mm). A total of 99 hollow, steel and hybrid fiber-reinforced CFCST, CFSST, and CFAT columns were tested under axial compression. The results showed that although the use of steel and synthetic fibers in single and hybrid form is very limited for enhancement of the axial load capacities of CFAT, CFCST and CFSST columns, the enhancement in ductility and post-peak toughness capacities are notable especially for CFCST and CFSST columns. However, the effects of steel and synthetic fibers on post-cracking behavior of the CFAT columns are not significant due to early rupture of AL tubes that cause highly brittle behavior after first peak load. In addition to this, the use of steel and synthetic fibers in hybrid form is slightly better at improving the ductility and toughness capacities of most of the CFAT, CFCST and CFSST columns than the use of steel fibers in single form.